Blockchain technology in supply chains: What are the opportunities for sustainable development? - Katharina Krings; Jakob Schwab (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
While blockchain technology (BT) has gained a great deal of publicity for its use in cryptocurrencies, another area of BT application has emerged away from the public eye, namely supply chains. Due to the increasing fragmentation and globalisation of supply chains in recent years, many products have to pass through countless production steps worldwide (from raw material extraction to the point of sale). Ensuring the quality and sustainability of production in preceding steps is a major challenge for many firms and thus, ultimately, also for the consumer. BT offers potential for achieving significant progress on this front. Put simply, the blockchain makes it possible to verify data decentralised within a network, store it in a tamper-proof and traceable format and make it accessible to all members of a network. The potential benefits of BT lie firstly with the consumer, who is able to trace the origin of products, which makes sustainable purchases easier. Secondly, BT enables producers to automate parts of their supply chains and to verify cost effectively the quality and origin of their products. Thirdly, there are hopes that BT could make supply chains more inclusive for small and medium-sized suppliers, especially in developing countries. BT also offers a means of more easily creating confidence in intermediate goods supplied, thereby dismantling barriers to entry. Taken together, BT could thus help to make consumption and production more environmentally friendly, socially equitable and inclusive, and thereby foster sustainable development. So far, pilot projects have received investment primarily from very large companies. Both the firms and their consumers can now audit a number of products in real time for manufacturing method and origin. While BT can securely store and chain together the inputted data, it cannot yet guarantee the accuracy of that data. This remaining challenge regarding the digital-analogue link could be addressed through links with other technologies, such as the Internet of Things (IoT). However, independent analogue audits are still the only means in most cases of checking compliance with labour, environmental, animal-welfare and other relevant standards. Consequently, the use of BT offers substantial potential benefits for sectors in which the digital-analogue link can be effectively bridged, such as the food and high-quality commodities sectors. Small-scale suppliers in developing countries also frequently lack the digital education, equipment and infrastructure needed in order to deploy BT. This is where national and international development policy is needed to leverage the benefits of BT solutions for inclusive production. General technological standards can also help to counteract the monopolisation of technological developments by multinational concerns. In this way, policy-makers could help to harmonise the interests of consumers and producers with those of small and medium-sized enterprises (SMEs) in the supply chain.
Keywords: 330; Blockchain; Lieferkette; Nachhaltige Entwicklung; Welt